Involvement of matrix metalloproteinases in chronic Q fever. (July 2017) - Jansen, A.F.M.; Schoffelen, T.; Textoris, J.; Mege, J.L.; Bleeker-Rovers, C.P.; Roest, H.I.J.; Wever, P.C.; Joosten, L.A.B.; Netea, M.G.; van de Vosse, E.; van Deuren, M.
Abstract: Objectives: Chronic Q fever is a persistent infection with the intracellular Gram-negative bacterium Coxiella burnetii, which can lead to complications of infected aneurysms. Matrix metalloproteinases (MMPs) cleave extracellular matrix and are involved in infections as well as aneurysms. We aimed to study the role of MMPs in the pathogenesis of chronic Q fever. Methods: We investigated gene expression of MMPs through microarray analysis and MMP production with ELISA in C. burnetii -stimulated peripheral blood mononuclear cells (PBMCs) of patients with chronic Q fever and healthy controls. Twenty single nucleotide polymorphisms (SNPs) of MMP and tissue inhibitor of MMP genes were genotyped in 139 patients with chronic Q fever and 220 controls with similar cardiovascular co-morbidity. Additionally, circulating MMPs levels in patients with chronic Q fever were compared with those in cardiovascular controls with and without a history of past Q fever. Results: In healthy controls, the MMP pathway involving four genes ( MMP1, MMP7, MMP10, MMP19 ) was significantly up-regulated in C. burnetii -stimulated but not in Escherichia coli lipopolysaccharide -stimulated PBMCs. Coxiella burnetii induced MMP-1 and MMP-9 production in PBMCs of healthy individuals (both p < 0.001), individuals with past Q fever (p < 0.05, p < 0.01, respectively) and of patients with chronic Q fever (both p < 0.001). SNPs in MMP7 (rs11568810) (p < 0.05) and MMP9 (rs17576) (p < 0.05) were more common in patients with chronic Q fever. Circulating MMP-7 serum levels were higher in patients with chronic Q fever (median 33.5 ng/mL, interquartile range 22.3–45.7 ng/mL) than controls (20.6 ng/mL, 15.9–33.8 ng/mL). Conclusion: Coxiella burnetii -induced MMP production may contribute to the development of chronic Q fever.